The relationships between job crafting, idiosyncratic deals, internal locus of control, psychological empowerment, and work engagement among Pakistani academicians: a moderated mediation model - Shams, Muhammad Shahid (2022)
This study aimed to investigate the mediating role of psychological empowerment on the relationship between job crafting, idiosyncratic deals and work engagement among academicians of Pakistani public universities. This study also examined the moderating effects of internal locus of control on job crafting–psychological empowerment and idiosyncratic deals–psychological empowerment relationships. The motivational process of job demands-resources (JD-R) theory was used to underpinned the study framework. A cross-sectional survey using the simple random sampling technique was carried out to elicit responses from the participants. Using an online survey, 324 useable responses were obtained which is 53.33% response rate. The data analysis was conducted using the Partial Least Square Structural Equation Modeling (PLS-SEM). The results indicated that both job crafting and idiosyncratic deals have a significant positive relationship with work engagement. Likewise, psychological empowerment partially mediated the relationship between job crafting, idiosyncratic deals, and work engagement. Interestingly, internal locus of control did not moderate the idiosyncratic deals–psychological empowerment relationship but did moderate the job crafting–psychological empowerment relationship. Counterintuitively, the relationship between job crafting and psychological empowerment became stronger when internal locus of control was high. Further, internal locus of control enhanced the indirect effect of job crafting on work engagement through psychological empowerment. However, the indirect effect of internal locus of control on the relationship between idiosyncratic deals and work engagement through psychological empowerment did not meet the standard for significance. Further, job crafting had a stronger effect on psychological empowerment and work engagement for academicians with an internal locus of control. The results show that the top management of the public universities need to consider the impact of psychological empowerment and internal locus of control to usurp these to enhance academicians’ work engagement.